THE CHALLENGES AND OPPORTUNITIES OF KURIKULUM MERDEKA IMPLEMENTATION IN INDONESIAN SCHOOLS - I Made Marthana Yusa; M. Yusuf; Ali Rahman; Aniati; Didik Supriyanto (Indonesian Journal of Education (INJOE), 2023)
This study examined the challenges and opportunities associated with implementing Curriculum Merdeka, a new curriculum reform initiative, in Indonesian schools. Data were collected from 20 teachers and ten school administrators across 15 schools in three provinces through semi-structured interviews and focus group discussions. The study found that the implementation of Kurikulum Merdeka faced challenges related to a lack of resources and infrastructure, inadequate training and support for teachers, and a heavy burden on teachers. However, the new curriculum also provided opportunities for more student-centered and interdisciplinary Learning, teacher professional development, and more significant equity and inclusion in Indonesian schools. The study recommends that policymakers and educators address the challenges of implementing Kurikulum Merdeka by providing adequate resources and support for teachers and clear guidance and expectations for the implementation process. Additionally, the study suggests that future research should examine the long-term impact of Kurikulum Merdeka on student learning outcomes and teacher professional development. Overall, this study highlights the importance of careful planning and support to implement new curriculum initiatives in Indonesian schools successfully.